” Bitin’ Back or the Importance of Being Ernest in Australia&#8221 - Polak, Iva (2007)
The novel Bitin’ Back by Indigenous Australian author Vivienne Cleven represents a specific turning point in Indigenous cultural production. Though light in tone, the novel challenges racial and gender prejudices in an imaginary small town community in the Australian outback. Focalized through the vivid vernacular of the protagonist, the Aboriginal mother, the text lays bare capacity of endurance of contemporary Indigenous identities avoiding the traditional demarcation of Indigenous identity as traditional vs. modern. By constructing Indigenous characters that are unstable from the point of view of race and gender, the text reveals a whole plethora of possible AND acceptable Indigenous identities in a contemporary Australian society notwithstanding the mainstream setting of the story.